HUBUNGAN POLA ASUH MAKAN DENGAN STATUS GIZI PADA BALITA USIA 1-3 TAHUN DIWILAYAH KERJA PUSKESMAS KAMBATA MAPAMBUHANG - Yonita Konga Naha; Widia Shofa Ilmiah (Journal of Innovative and Creativity (Joecy), 2026)
The toddler period represents a critical phase in child growth and development. This stage is characterized by remarkably rapid developmental progress, which is why it is often referred to as the golden period in the human life cycle. The success of toddler growth and development is influenced by various factors, particularly the feeding practices applied by parents and the child's nutritional status. This study aimed to analyze the relationship between feeding practices and macronutrient intake with the nutritional status of toddlers in the working area of the Kambata Mapambuhang Health Center. A quantitative method with a cross-sectional design was employed. The study population consisted of 437 toddlers, from which 94 respondents were selected using proportional random sampling. Data analysis was conducted using the Chi-Square test. The findings revealed that out of 94 respondents, 78 (83%) applied good feeding practices for their toddlers, while 79 (84%) had good nutritional status. Statistical analysis demonstrated a significant relationship between feeding practices and toddler nutritional status in the working area of the Simpang Kawat Health Center, with a p-value of 0.000. Therefore, parents, especially mothers, are expected to pay greater attention to children's feeding practices to ensure that toddler nutritional status remains optimally maintained